Clinical validity of the nerve root sedimentation sign in patients with suspected lumbar spinal stenosis - Barz, T.; Staub, L.; Melloh, Markus; Hamann, G.; Lord, S.; Chatfield, M.; Bossuyt, P.; Lange, J.; Merk, H. (Elsevier Inc., 2014)
Background context: The nerve root sedimentation sign in transverse magnetic resonance imaging has been shown to discriminate well between selected patients with and without lumbar spinal stenosis (LSS), but the performance of this new test, when used in a broader patient population, is not yet known. Purpose: To evaluate the clinical performance of the nerve root sedimentation sign in detecting central LSS above L5 and to determine its potential significance for treatment decisions. Study design: Retrospective cohort study. Patient sample: One hundred eighteen consecutive patients with suspected LSS (52% women, median age 62 years) with a median follow-up of 24 months. Outcome measures: Oswestry disability index (ODI) and back and leg pain relief. Methods: We performed a clinical test validation study to assess the clinical performance of the sign by measuring its association with health outcomes. Subjects were patients referred to our orthopedic spine unit from 2004 to 2007 before the sign had been described. Based on clinical and radiological diagnostics, patients had been treated with decompression surgery or nonsurgical treatment. Changes in the ODI and pain from baseline to 24-month follow-up were compared between sedimentation sign positives and negatives in both treatment groups. Results: Sixty-nine patients underwent surgery. Average baseline ODI in the surgical group was 54.7%, and the sign was positive in 39 patients (mean ODI improvement 29.0 points) and negative in 30 (ODI improvement 28.4), with no statistically significant difference in ODI and pain improvement between groups. In the 49 patients of the nonsurgical group, mean baseline ODI was 42.4%; the sign was positive in 18 (ODI improvement 0.6) and negative in 31 (ODI improvement 17.7). A positive sign was associated with a smaller ODI and back pain improvement than negative signs (both p<.01 on t test). Conclusions: In patients commonly treated with decompression surgery, the sedimentation sign does not appear to predict surgical outcome. In nonsurgically treated patients, a positive sign is associated with more limited improvement. In these cases, surgery might be effective, but this needs investigation in prospective randomized trials (Australian New Zealand Clinical Trial Registry, number ACTRN12610000567022). © 2014 Elsevier Inc. All rights reserved.